PRENYLATED FLAVONOID FROM TWIG BARK OF ARTOCARPUS CAMANSI (KLUWIH) AND THEIR ANTIBACTERIAL ACTIVITIES - Ardhi Rosyadi, Imam
One of the plant genus that is known to have benefits in traditional medicine, such as for treating toothache, canker sores, and skin infections, is Artocarpus (nangkanangkaan) from the Moraceae family. This genus consists of 50 species and is spread throughout several regions such as Indonesia, South Asia, Southeast Asia, the Solomon Islands, the Pacific Islands, North Australia, and Central America. Species of this genus are known as fruit and wood-producing plants that have economic value. Artocarpus is known as a plant that contains prenylated flavonoids as the main secondary metabolites. Prenylated flavonoids from this genus are known to have diverse bioactivities, such as anticancer, antibacterial, antimalarial, antioxidant, and antiinflamatory. Artocarpus camansi is a species of the genus Artocarpus that grows in Indonesia. Based on a literature review, A. Camansi extract showed several bioactivities, including antioxidant, antibacterial, and antidiabetic activities. So far, the studies of the phytochemistry of A. camansi has only examined the leaves and stem. The secondary metabolites that have been reported are only terpenoids and steroids. The phytochemistry and bioactivity studies of the twig bark of A. camansi has never been reported. Based on these, this study aimed to isolate secondary metabolites from the twig bark of A. camansi from West Java and examine the anti-bacterial bioactivity of the isolated compounds. The methods used include extraction using acetone solvent, separation and purification using vacuum liquid chromatography (VLC), radial chromatography (RC), and gravity column chromatography (GCC), as well as determining the structure of the isolated compound using one-dimensional NMR spectroscopy data (1H NMR and 13C NMR), two-dimensional NMR (HSQC and HMBC). The isolated compounds were examined for antibacterial activity against Enterococcus faecalis and Proteus mirabilis bacteria using the agar dilution assay method. Four flavonoid compounds, cycloartobiloxanthone, morusin, artonin E 2’-methylether, and artonin E as well as one steroid derivative compound, ?-sitosterol were isolated in this study. Cycloartobiloxanthone is the main compound in the twig bark of A. camansi. These four prenylated flavonoid compounds were first reported from A. camansi. The antibacterial activity test of the isolated compounds showed that the four flavonoid compounds could inhibit the growth of E. faecalis and P. mirabilis bacteria with ampicillin as a positive control, while one steroid compound was inactive. Artonin E 2'-methylether showed better inhibition activity against E. faecalis and P. mirabilis compared to the other three flavonoids with inhibition zone values of 11,33 ± 1,04 mm and 9,83 ± 0,76, respectively.